Розробка нейро інформаційної системи керування електротехнічним комплексом пташника - Горобець, В. Г.; Троханяк, В. І.; Антипов, Є. О.; Богдан, Ю. О. (Energy and Automation, 2017)
Neuro DEVELOPMENT MANAGEMENT INFORMATION SYSTEM ELECTRIC AND HARDWARE aviaryV. Gorobets, V. Trohanyak, I. Antypov, Y. Bogdan At the present stage of development of the energy sector of Ukraine important issue is to increase the capacity of energy and energy efficiency in all sectors of industry and agriculture. The rapid development of the poultry industry in the agricultural sector of Ukraine, which is observed in the last period of time associated with the important issue of improving the microclimate in keeping poultry indoors. This is due to the need to improve productivity and reduce cost of production poultry complexes. These issues are inextricably linked with the use of modern methods of energy facilities and advanced means of energy supply and alternative energy sources. So important is the development of new approaches and improving electrical systems for existing power systems poultry.The purpose of research - development of information system management neuro complex electrical poultry house using low potential energy of water underground drillholes from experimental studies.After analyzing the hybrid network can rightly conclude its adequacy. The surface represents for network features 1 with fluctuations in ambient temperature range from +23 to +40 ° C and water flow necessary for cooling supply air in the poultry house from 2 to 108 m3 / h, visualization of the interaction of all parameters. The trained ANFIS provides the required accuracy of the coefficient of water flow and can be used to control the electrical complex ventilation and microclimate poultry house.Conclusions i prospects. The model ANFIS neyroinformatsiyna network, depending on the outdoor temperature of air flow needed to provide the necessary microclimate poultry house and water consumption for cooling supply air showed its adequacy, mean-error system configuration was 6.5753 Testing data processing at 4.8331 and the processing Cheking data. The trained ANFIS provides the required accuracy of the coefficient of water flow and can be used to control the electrical complex ventilation and microclimate poultry house.